Analysis of Business Risk in Consumption Fish Rearing in Putat Nutug Village, Ciseeng District Bogor Regency - Syahrial, Relfy; Yoesdiarti, Arti; Kusumawati, Rini (JURNAL AGRIBISAINS, 2026)
This study aims to analyze the aquaculture risks in the grow-out phase of consumption fish (Catfish and Gourami) in Putat Nutug Village, Bogor Regency, using the Failure Mode and Effect Analysis (FMEA) method to identify and prioritize major risks based on the Risk Priority Number (RPN) value. The FMEA results show that the three risks with the highest RPN in Catfish aquaculture are extreme weather changes (RPN 306.14), rising feed prices (RPN 288.96), and disease outbreaks (RPN 274.67). Meanwhile, the highest risks in Gourami aquaculture are extreme weather changes (RPN 468.22), rising feed prices (RPN 326.67), and natural disasters (RPN 301.01). Overall, external factors such as the natural environment and market dynamics are the main determinants of risk. The risk mitigation implemented by farmers includes technical strategies (water quality management, alternative feed) and managerial strategies (utilization of BMKG information, collective purchasing, fishery insurance), but it is recommended to focus on sustainable environmental management and government infrastructure support to minimize potential risks influenced by natural conditions.